2007
DOI: 10.1038/nm1617
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP triggers and maintains asthmatic airway inflammation by activating dendritic cells

Abstract: Extracellular ATP serves as a danger signal to alert the immune system of tissue damage by acting on P2X or P2Y receptors. Here we show that allergen challenge causes acute accumulation of ATP in the airways of asthmatic subjects and mice with experimentally induced asthma. All the cardinal features of asthma, including eosinophilic airway inflammation, Th2 cytokine production and bronchial hyper-reactivity, were abrogated when lung ATP levels were locally neutralized using apyrase or when mice were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
575
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 553 publications
(598 citation statements)
references
References 49 publications
23
575
0
Order By: Relevance
“…oATP was successfully applied to limit T cellmediated inflammation in mouse models of type 1 diabetes and inflammatory bowel disease [29,118]. oATP, suramine, and pyridoxalphosphate-6-azophenyl-2′,4′-disulphonic acid significantly reduced allergic airway inflammatory response in the OVA-mediated model of asthma [91]. Thus, purinergic receptor blockade might represent a promising therapeutic strategy for the treatment of a number of inflammatory diseases including allergy in which mast cells are recognized to play an effector role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…oATP was successfully applied to limit T cellmediated inflammation in mouse models of type 1 diabetes and inflammatory bowel disease [29,118]. oATP, suramine, and pyridoxalphosphate-6-azophenyl-2′,4′-disulphonic acid significantly reduced allergic airway inflammatory response in the OVA-mediated model of asthma [91]. Thus, purinergic receptor blockade might represent a promising therapeutic strategy for the treatment of a number of inflammatory diseases including allergy in which mast cells are recognized to play an effector role.…”
Section: Discussionmentioning
confidence: 99%
“…2). In fact, recent observation shows that ATP levels are significantly elevated in the airways of asthmatic patients after allergen challenge and in mice in a model of ovalbumin (OVA)-induced asthma [91]. Aerosolized ATP triggers bronchoconstriction in healthy and asthmatic individuals [92].…”
Section: Purinergic Signaling In Allergic Airway Inflammation: Focus mentioning
confidence: 99%
“…ATP is reported to be important for the genesis and maintenance of this disease. For instance, ATP triggers and maintains asthmatic inflammation by activating DCs and enhancing its Th2-priming capacity [134,135]. Another study demonstrated that this allergic inflammation in humans and mice is associated with the functional up-regulation of P2X7 receptor expression on immune cells (macrophages and eosinophils) and that P2X7 receptor signaling (e.g., via modulating of DC function) is involved in ATP-mediated pro-asthmatic effects [136].…”
Section: Pulmonary Epithelium Injurymentioning
confidence: 99%
“…Extracellular Ado appears to be an important immunosuppressive and tissue-healing factor. Like ATP, Ado can also be considered a danger molecule because its extracellular levels rise markedly in response to tissue damage [13,66,122].…”
Section: Immunomodulation and Cell-cell Interactionsmentioning
confidence: 99%